Stereocontrolled 1,3-nitrogen migration to access chiral α-amino acids - Ye, Chen-Xi; Shen, Xiang; Chen, Shuming; Meggers, Eric (Nature chemistry, 2022)
α-Amino acids are essential for life as building blocks of proteins and components of diverse natural molecules. In both industry and academia, the incorporation of unnatural amino acids is often desirable for modulating chemical, physical and pharmaceutical properties. Here we report a protocol for the economical and practical synthesis of optically active α-amino acids based on an unprecedented stereocontrolled 1,3-nitrogen shift. Our method employs abundant and easily accessible carboxylic acids as starting materials, which are first connected to a nitrogenation reagent, followed by a highly regio- and enantioselective ruthenium- or iron-catalysed C( sp 3 )–H amination. This straightforward method displays a very broad scope, providing rapid access to optically active α-amino acids with aryl, allyl, propargyl and alkyl side chains, and also permits stereocontrolled late-stage amination of carboxylic-acid-containing drugs and natural products. A straightforward method for synthesizing optically active α-amino acids from abundant carboxylic acids has been developed. Based on a nitrene-mediated stereocontrolled 1,3-nitrogen shift, this approach provides access to a large variety of unnatural α-amino acids with aryl, allyl, propargyl and alkyl side chains and enables late-stage amination of carboxylic-acid-containing drugs.